COLLABORATIVE GOVERNANCE DALAM PENANGANAN PENGUNGSI DI KOTA PEKANBARU TAHUN 2022-2023 - Hariyanti, Mutiara Wita; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia is a transit point for refugees to their destination countries. Pekanbaru City is one of the cities where there are quite a lot of refugees from various countries. Due to the large number of refugees in Pekanbaru, there are several problems that occur, especially in the areas of security, order and data collection, namely demonstrations by refugees, traffic violations and using vehicles illegally, refugees leaving accommodation and not returning, security forces do not dare to reprimand refugees who are late returning home, there is no certainty regarding the resettlement time by UNHCR. This research aims to find out how the Collaborative Governance process will be in handling refugees in Pekanbaru City in 2022-2023. This research is descriptive research with a qualitative approach. The types of data include primary data and secondary data, with primary data obtained directly from informants. Meanwhile, secondary data is data that supports or perfects primary data. Data collection techniques are carried out through interviews and documentation. The data analysis technique used is inductive qualitative data analysis. The results of the research show that before the formation of the PPLN task force through Mayor Decree Number 153 of 2023 concerning the Task Force for Handling Refugees from Abroad in Pekanbaru City, in handling refugees, every stakeholder had not participated fully even though it was already in Law Number 125 of 2016, more precisely, there were no regulations that tie them up. After the Mayor's Decree Number 153 of 2023, every stakeholder is bound to carry out the task of handling refugees and be better than before the formation of the task force. Second, the application of Collaborative Governance theory has gone well, but there are still stakeholders who are still confused about their duties. Then the collective activities start from discovery until the refugees reach their destination. Lastly, the collaborative success factor is almost perfect, but for resources both quantity & quality of resources is still lacking as well as budget resources. Keywords: Collaborative Governance, Refugees, stakeholders